2007
DOI: 10.1097/00000542-200703000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Cognitive Dysfunction in Older Patients with a History of Alcohol Abuse

Abstract: Background: Postoperative cognitive dysfunction (POCD) affects a significant number of patients and may have serious consequences for quality of life. Although POCD is most frequent after cardiac surgery, the prevalence of POCD after noncardiac surgery in older patients is also significant. The risk factors for POCD after noncardiac surgery include advanced age and preexisting cognitive impairment. Self-reported alcohol abuse is a risk factor for postoperative delirium, but its significance for long-term POCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 61 publications
1
33
1
5
Order By: Relevance
“…Several other risk factors, including lower educational level, a history of previous cerebral vascular accident, POCD at hospital discharge [15], the postoperative pain treatment regimen [19], and a history of alcohol abuse [20] are reported to infl uence the occurrence and severity of POCD at varying postoperative intervals.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Several other risk factors, including lower educational level, a history of previous cerebral vascular accident, POCD at hospital discharge [15], the postoperative pain treatment regimen [19], and a history of alcohol abuse [20] are reported to infl uence the occurrence and severity of POCD at varying postoperative intervals.…”
Section: Risk Factorsmentioning
confidence: 99%
“…These patients may also experience impaired self-care, increased dependency, increased attrition from rehabilitation, and higher rates of hospital readmission. Advanced age, low educational level, preexisting cognitive impairment, alcohol abuse, and severity of coexisting illness are risk factors for POCD [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…3 To further substantiate the controversy regarding alcohol and dementia, other reports even highlight reduced rates of dementia when comparing alcohol drinkers with nondrinkers. 4,5 Specific to the context of surgery, Hudetz et al 6,7 have reported on the role of alcohol dependence and postoperative cognitive dysfunction after both cardiac and noncardiac surgery. In this setting, the association with postoperative cognitive dysfunction was made on selective neurocognitive domains (eg, visuospatial and executive functions), and alcohol abuse was described as an additional factor in cognitive decline.…”
Section: Influence Of Alcohol On Perioperative Cognitive Declinementioning
confidence: 99%